ALJABAR-C* KOMUTATIF - Batkunde, Harmanus (PATTIMURA UNIVERSITY, 2013)
These notes in this paper will discuss about C*-algebras commutative and its properties. The theory of algebra-*, Banach-* algebra, C*-algebras and *-homomorphism are included. We also give some examples of commutative C*-algebras. We shall prove and discuss some important properties of commutative C*-algebras and *-homomorphism.